The weighted product method and portfolio assessment in ranking student achievement - Andi Tenri Sumpala; Muhammad Nurtanzis Sutoyo; Huzain Azis; Fadhila Tangguh Admojo (ILKOM Jurnal Ilmiah, 2021)
The learning process has a correlation with learning achievement which can be shown through the marks given by a teacher to students from several fields of study. The ranking of student learning achievements performed by the school refers to the grades of the subject is important for the SNMPTN (National Selection for State Higher Education). To determine student achievements, the method used in the current study is the weighted product. If the results of student ranking using the WP method have the same value, then a portfolio assessment is used. Of the 127 student achievement ratings, there were seven people who had the same Vector value. Then, the seven people who have the same vector value were graded using portfolio assessment. The results showed that the implementation of the WP method and portfolio assessment could determine the ranking of student achievement.